Análisis del sistema defensivo en primera línea en voley playa femenino - Gea, G. M.; Molina, J. J. (Revista Internacional de Ciencias del Deporte, 2013)
The defense of the net is considered a discriminatory action of the victory in the game. Therefore, the aim of this study was to analyze the defense of the net actions in women`s beach volleyball. The main variables analyzed were the defensive game system, the game level exhibited by participating couples and their classification in the game. The sample was consisted of 38 players, divided according to their level of play, in 13 couples with national level, and 6 international level (players who compete in internationals tournaments representing Spain). 15 games were analyzed, recording 1.444 complete sequences in defense of the net. A study of confiability was carried out, to determine the degree of agreement inter and intraobservers, reaching to achieve agreement between observers >.80, wich guarantees the quality of data. Correlational analysis results showed a difference in the defensive system used, showing test of Chi - Square of Person significance in the crossing of the variables studied (.² of Pearson <.05). Couples showed a clear trend in the block areas, which together with previous results, creates a pattern of behavior related to blocking the hitting zone of the ball on offense, which is a clear advantage in the game, through the anticipated movement of the player blocking. National couples, which classified like no finalist, showed more failed in block.